Global Research on Digital Platforms in Rural Knowledge Transfer During 2003-2025: A Bibliometric Analysis - Dhillon, Dr. Manju (Indian Journal of Extension Education, 2025)
The study mapped global research on digital platforms in rural knowledge transfer using Scopus-indexed publications published between 2003 and 2025. A total of 251 peer-reviewed documents were analysed using descriptive indicators, citation patterns, and network visualisations. The analysis indicated a consistent increase in research output after 2015, with notable peaks in 2021 and 2023, reflecting the growing adoption of ICTs, mobile applications, and e-learning in agricultural extension. Highly cited publications demonstrated strong scholarly influence in digital learning and technology-enabled advisory frameworks. Country-level analysis identified the United States, China, and the United Kingdom as leading contributors, supported by key institutions such as Wageningen University and the International Institute of Tropical Agriculture (IITA). Keyword co-occurrence mapping revealed dominant themes related to digital agriculture, mobile-based extension, AI-enabled learning, and knowledge management, alongside emerging areas such as digital literacy and participatory knowledge systems. Despite India’s extensive digital agriculture initiatives, the limited presence of high-impact Indian studies highlights a critical research gap. The findings underscore the need for context-specific and inclusive digital extension research in India, while outlining future prospects focused on impact evaluation, digital literacy, and participatory platform design.